2012
DOI: 10.1016/j.vetmic.2011.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Coxiella burnetii seroprevalence in macropods in Australia

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 ELISAs were developed for the testing of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
(14 reference statements)
3
25
0
Order By: Relevance
“…Similar high prevalence rates of Q fever were reported in 1960 in kangaroos in western Queensland 10. Recent kangaroo seroprevalence studies reported in 2012 showed similar high prevalence rates (11% to 25% near Ipswich, and up to 40% in areas near our case) 9. Although association does not prove causality, our patient's repeated exposure to carcases of kangaroos and wallabies as part of her work was a potential source of infection.…”
Section: Discussionsupporting
confidence: 87%
“…Similar high prevalence rates of Q fever were reported in 1960 in kangaroos in western Queensland 10. Recent kangaroo seroprevalence studies reported in 2012 showed similar high prevalence rates (11% to 25% near Ipswich, and up to 40% in areas near our case) 9. Although association does not prove causality, our patient's repeated exposure to carcases of kangaroos and wallabies as part of her work was a potential source of infection.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison, general populations in Australia report a seroprevalence of two to five per cent in metropolitan areas (Gidding et al, ; Tozer et al, ). This is supported by reports of Q fever outbreaks associated with cat and dog births (Gibbons & White, ; Kopecny et al, ; Malo et al, ), Q fever disease among cat breeders (Shapiro, Norris, Bosward, & Heller, ), and the detection of C. burnetii in a large variety of domestic and wild animal species in Australia (Cooper, Barnes, Potter, Ketheesan, & Govana, ; Shapiro, Bosward, Heller, & Norris, ; Shapiro, Norris, Heller, & Bosward, ; Tozer et al, ). While reports of disease associated with non‐ruminant species and within metropolitan areas are low, the consequence of clinical Q fever disease for those affected may be severe.…”
Section: Discussionmentioning
confidence: 62%
“…37 Macropod seropositivity to C. burnetii in Queensland and western Australia has been reported. 38 Several Australian tick species have been shown to contain C. burnetii DNA 39 including A. triguttatum (from macropods) and Haemaphysalis humerosa (from bandicoots, which are known to be an important reservoir for C. burnetii). Ixodes holocyclus, the paralysis tick, which is the main human-biting tick in Australia and Bothriocroton auruginans, the wombat tick, also harbor C. burnetii.…”
Section: Discussionmentioning
confidence: 99%